Systematic Review of Social Support on Psychological Symptoms and Self‐Management Behaviors Among Adults With Inflammatory Bowel Disease. Issue 4 (22nd May 2019) - Kamp, Kendra J.; West, Patricia; Holmstrom, Amanda; Luo, Zhehui; Wyatt, Gwen; Given, Barbara
Abstract: Purpose: The purpose was to determine the relationship between social support, psychological symptoms and self‐management behaviors among adults with inflammatory bowel disease (IBD) and examine the influence of types of social support and patient age. Design: This was a systematic review. PubMed, Web of Science, Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO, Communication and Mass Media Complete, and Communication Abstracts were searched. Publication dates were limited to January 2000 to August 2018. Methods: The systematic review was guided by the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis statement, and quality was appraised based on the Critical Appraisal Skills Programme for cohort studies tool. The data were synthesized using narrative synthesis techniques. Findings: The literature review yielded 458 results. Eight articles met inclusion criteria. Articles utilized a variety of conceptualizations of both social support and self‐management behaviors, making comparisons difficult. Findings demonstrated an inverse relationship between social support and psychological symptoms, and in one study only when social support buffered high stress. Studies with significant relationships between age and self‐management behaviors indicated that a lower age was associated with decreased self‐management behaviors. Conclusions: Social support has the potential to influence psychological symptoms among patients with IBD. Future research should examine types of social support (i.e., emotional, informational, and tangible support) and measure levels of received social support. Clinical Relevance: Social support may serve as a modifiable factor to improve psychological symptoms among adults with IBD. Younger adults (age <40 years) may benefit from specialized interventions to address self‐management behaviors.